2019
DOI: 10.1016/s2589-7500(19)30082-2
|View full text |Cite
|
Sign up to set email alerts
|

Chat-based instant messaging support integrated with brief interventions for smoking cessation: a community-based, pragmatic, cluster-randomised controlled trial

Abstract: Background Mobile instant messaging apps offer a modern way to deliver personalised smoking cessation support through real-time, interactive messaging (chat). In this trial, we aimed to assess the effect of chat-based instant messaging support integrated with brief interventions on smoking cessation in a cohort of smokers proactively recruited from the community. Methods In this two-arm, pragmatic, cluster-randomised controlled trial, we recruited participants aged 18 years or older who smoked at least one cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 61 publications
(99 citation statements)
references
References 33 publications
8
74
2
Order By: Relevance
“…This is often considered unnecessary in population-based trials of smoking cessation interventions with minimal contact between the investigators and participants [25]. The participation rate in the validation was approximately 51.1%, which was acceptable and comparable to our previous studies [11,15] and trials conducted in similar settings elsewhere [10]. The participation rates were similar among the three study groups, and the relative effect sizes of self-reported and bio-verified abstinence outcomes were homogeneous.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…This is often considered unnecessary in population-based trials of smoking cessation interventions with minimal contact between the investigators and participants [25]. The participation rate in the validation was approximately 51.1%, which was acceptable and comparable to our previous studies [11,15] and trials conducted in similar settings elsewhere [10]. The participation rates were similar among the three study groups, and the relative effect sizes of self-reported and bio-verified abstinence outcomes were homogeneous.…”
Section: Discussionsupporting
confidence: 72%
“…A significantly higher cumulative rate of the use of a smoking cessation service was observed in the OSR group than in the less intensive TMR and control groups. This, coupled with our observation that the use of a smoking cessation service is associated with increased abstinence at 6 months [15], suggested that the higher 6-month abstinence rate was attributable to the greater use of smoking cessation services in the OSR group than in the control group. However, the TMR group had a higher abstinence rate than the control group, despite a similar rate in the use of smoking cessation services.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations